ANALISIS PENGARUH GEOMETRI JALAN PIT MAJAPAHIT BESERTA TOTAL RESISTANCE TERHADAP SPEED DAN FUEL RATIO KOMATSU HD 785-7 PT. KALIMANTAN PRIMA PERSADA SITE PCN DESA SEBAMBAN KEC. SUNGAI LOBAN KAB. TANAH BUMBU KALIMANTAN SELATAN - Lukman Firmansyah; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2022)
Abstract. PT. Kalimantan Prima Persada is a coal mining company, one of its working locations is PT. PCN (Prolindo Cipta Nusantara) The mining pit is named the Majapahit Pit. At the Majapahit Pit, a new road was built that functions for the overburden transportation road, namely Jalan Arjunasastra and Jalan Putri Gunung Buih.Many road segments have non-ideal road geometry, based on speed data of Komatsu HD 785-7 loaded and unloaded equipment it was found that 35.48 km/hour and 12.01 km/hour. This is not in accordance with the company's target, where the target speed of the HD 785-7 conveyance is 17 km/hour and 50 km/h empty. As a result of not achieving the speed, it will affect the production of transportation equipment in March-April, based on data on the production of Komatsu HD 785-7 transportation equipment, which is actually 231.860 Bcm but the company's target is 288.000 Bcm. As a result of not achieving production, it affects the value of the fuel ratio of the conveyance. Based on fuel ratio data, the actual conveyance is 0.68 Bcm/hour but the company's target is 0.54 Bcm/hour.The effect of total resistance on speed is inversely proportional, meaning that if the total resistance increases, the speed decreases. And the effect of total resistance on the fuel ratio is directly proportional, meaning that if the total resistance increases, the fuel ratio increases. This is in accordance with the results of the improvement. After repairs were made, it was found that the speed value for the loaded condition increased to 17.91 Km/hour and the empty condition became 50.05 Km/hour so that it increased by about 40%, for the production of transportation equipment it increased to 294,307 Bcm/hour so that it rose 23,52% and fuel ratio decreased to 0.54 Bcm/hour so that the fuel ratio decreased by 25,93%.